K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

16 tháng 9 2019

3²\0,375² = (3\0375)² = 8² = 64

Học tốt←

4 tháng 7 2018

\(a)3^{x+1}-3^x=162\)

\(\Leftrightarrow3^x\cdot3-3^x=162\)

\(\Leftrightarrow3^x\left(3-1\right)=162\)

\(\Leftrightarrow3x\cdot2=162\)

\(\Leftrightarrow3x=162:2\)

\(\Leftrightarrow3x=81\)

\(\Leftrightarrow x=81:3\)

\(\Leftrightarrow x=27\)

Vậy x=27

\(b)\left(1-x\right)^3=216\)

\(\Leftrightarrow\left(1-x\right)^3=6^3\)

\(\Leftrightarrow x-1=6\)

\(\Leftrightarrow x=6+1\)

\(\Leftrightarrow x=7\)

Vậy x=7

\(c)5^{x+1}-2\cdot5^x=375\)

\(\Leftrightarrow5^x\cdot5-2\cdot5^x=375\)

\(\Leftrightarrow5^x\cdot\left(5-2\right)=375\)

\(\Leftrightarrow5^x\cdot3=375\)

\(\Leftrightarrow5^x=375:3\)

\(\Leftrightarrow5^x=125\)

\(\Leftrightarrow5^x=5^3\)

\(\Leftrightarrow x=3\)

Vậy x=3

5 tháng 12 2015

32010- ( 32009 + 32008 + ... + 3 + 1 )

Đặt A = 1 + 3 + ... + 32009

=> 3A = 3 + 32 + ... + 32010

=> 3A - A = 32010 - 1

Nên 32010 - ( 32010 - 1 ) = 1

29 tháng 7 2018

\(5^{x+1}-2.5^x=375\Rightarrow5^x.5-2.5^x=375\Rightarrow3.5^x=375\Rightarrow5^x=125=5^3\Rightarrow x=3\)

29 tháng 7 2018

5x.5-2.5x=375

5x. (5-2)=375

5x=125

x=3

11 tháng 6 2018

\(2^3+3.\left(\frac{1}{9}\right)^0-2.4+\left[\left(-2\right)^2:\frac{1}{2}\right].8\)

\(=8+3.1-8+\left(4:\frac{1}{2}\right).8\)

\(=\left(8-8\right)+3+8.8\)

\(=3+64=67\)

15 tháng 3 2017

\(A=\left(-3\right)^0+\left(-3\right)^1+\left(-3\right)^2+.....+\left(-3\right)^{2004}\)

\(-3A=\left(-3\right)^1+\left(-3\right)^2+...+\left(-3\right)^{2005}\)

\(-3A-A=\left(-3^{2005}-\left(-3^0\right)\right)\)

\(A=\frac{\left(-3^{2005}-\left(-3^0\right)\right)}{-4}\)

15 tháng 3 2017

3A= (-3)^2005 - (-3) ^ 0

3 tháng 4 2017

1)3x4-5x3y+6x2-10xy+2

=(3x4-5x3y)+(6x2-10xy)+2

=x3(3x-5y)+2x(3x-5y)+2

=x3.0+2x.0+2

=0+0+2

=2

2) x5-2010x4+2010x3-2010x2+2010x-2020

=x5-(2009+1)x4+(2009+1)x3-(2009+1)x2+(2009+1)x-2009-11

=x5-(x+1)x4+(x+1)x3-(x+1)x2+(x+1)x-x-11

=x5-x5-x4+x4+x3-x3-x2+x2+x-x-11

=-11

18 tháng 3 2018

2, Với x= 2009 => 2010=x+1

=> \(x^5-2010\text{x}^4+2010\text{x}^3-2010\text{x}^2+2010\text{x}-2020=x^5-\left(x+1\right)x^4+\left(x+1\right)x^3-\left(x+1\right)x^2+\left(x+1\right)x-2020\)

\(=x^5-x^5-x^4+x^4+x^3-x^3-x^2+x^2+x-2020\)

\(=x-2020\)

\(=2009-2020\\ =-11\)